Serum enzyme profile in post parturient bovines suffering from anorexia and ketosis - AGARWAL, R G; JADIA, J K; QUADRI, M A; SHARMA, I J; PANDIT, R K (The Indian Journal of Animal Reproduction, 2023)
Fifty two postparturient animals included in this study. The serum levels ofGl-6 Pase were higher in the anorectic bovines and ketotic buffaloes, particularly, around 2 months lactation. The serum levels ofliver specific enzymes, viz., GOT, GPT and SAP were also recorded to be on higher side during anorexia and ketosis. However, the levels of acetylcholinesterase were low in the anorectic and ketotic animals. The treatment of the anorexic and ketotic animals with propylene glycol reversed back the enzymatic changes in the sera samples of these animals.